More progresses in analysis : proceedings of the 5th International ISAAC Congress, Catania, Italy, 25-30 July 2005 - Begehr, Heinrich G. W.; Nicolosi, Francesco, 1938- (World Scientific, 2009)
International ISAAC (International Society for Analysis, its Applications and Computation) Congresses have been held every second year since 1997. The proceedings report on a regular basis on the progresses of the field in recent years, where the most active areas in analysis, its applications and computation are covered. Plenary lectures also highlight recent results. This volume concentrates mainly on partial differential equations, but also includes function spaces, operator theory, integral transforms and equations, potential theory, complex analysis and generalizations, stochastic analysi.